The past in the present : a mixed methods evaluation of a group intervention for loneliness and well-being among older people : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Wellington, New Zealand - Miclette, Isabelle (Massey University, 2011)
Recent research has shown loneliness in old age to be a major risk factor for a variety of deleterious psychological and physiological outcomes, including cognitive decline, progression of Alzheimer‟s disease, increased blood pressure, depression, and mortality. However, practical interventions which meet reasonable standards in terms of feasibility and outcome are limited. The main purpose of this study was to develop and evaluate the usefulness of a brief instrumental reminiscence intervention aimed at preventing and alleviating loneliness to increase the well-being of older people. A mixed methods design allowed the examination of both the impact and process of the intervention, as experienced by four groups of older people living in a retirement facility in New Zealand (N = 17; mean age = 84 years). Loneliness and well-being were assessed over five measurement points with the short form of the Social and Emotional Loneliness Scale for Adults, and Affectometer 2, respectively. Repeated measures analysis of variance, content analysis, and thematic analysis were employed to investigate the participants‟ experience of the intervention. Results showed a high level of satisfaction with the intervention, and provided preliminary evidence for its usefulness over a time period of two months. Loneliness was conceptualised by participants as a normal challenge of life which can be actively addressed by connecting with others in meaningful ways. Learning for participants was located primarily in their experience of the intervention, namely from relationships developed within the groups themselves. This study offers support for the theory on social and emotional loneliness, substantiates the acceptability and usefulness of practical group interventions to enhance well-being in later life, and highlights the importance of tailoring interventions to the needs and experiences of older people. In light of the emphasis study participants placed on group therapeutic factors as their primary source of learning about coping with loneliness, future interventions could focus on the role of feedback and social comparison in promoting connectedness amongst older people.

Des recherches récentes ont démontré que la solitude chez les personnes âgées est un facteur de risque important pour une variété de problèmes psychologiques et physiologiques, y compris le déclin cognitif, la progression de la maladie d‟Alzheimer, l‟hypertension, la dépression et la mortalité. Cependant, très peu d‟interventions concrètes, répondant à des normes raisonnables en termes de faisabilité et d‟efficacité, ont été développées. L‟objectif principal de cette étude était d‟élaborer et d‟évaluer l'utilité d'une brève intervention comprenant la rétrospective de vie instrumentale visant à prévenir et à atténuer la solitude en vue d'accroître le bien-être des personnes âgées. Une conception de méthodes mixtes a permis d‟évaluer l'impact et le processus de l‟intervention, telle que considérée par quatre groupes de personnes âgées vivant dans une maison de retraite en Nouvelle-Zélande (N = 17, âge moyen = 84 ans). La solitude et le bien-être ont été mesurés sur une échelle de cinq points avec la Social and Emotional Loneliness Scale for Adults (version abrégée), et Affectometer 2, respectivement. Une analyse de la variance à mesures répétées, une analyse de contenu, et une analyse thématique ont été utilisées pour étudier l‟expérience de l‟intervention par les participants. Les résultats ont montré un niveau élevé de satisfaction à l'égard de l‟intervention, et ont fourni des preuves préliminaires pour son utilité sur une période de deux mois. La solitude a été conceptualisée par les participants comme un défi normal de la vie qui peut être relevé de manière active, en développant des relations interpersonnelles satisfaisantes. L‟apprentissage pour les participants était localisé principalement dans leur expérience de l‟intervention, à savoir dans les interactions au sein des groupes. Cette étude supporte la théorie de la solitude sociale et affective, démontre l‟utilité des interventions de groupes concrètes en vue d‟améliorer le bien-être des personnes âgés, et souligne l‟importance d'adapter les interventions psychologiques aux besoins spécifiques des individus et à leurs expériences respectives. L‟accent mis par les participants sur les facteurs thérapeutiques de groupe comme source primaire d‟apprentissage pour vivre avec la solitude suggère que de futures interventions pourraient porter sur l‟importance du feedback et de la comparaison sociale en vue de promouvoir la connexion parmi les personnes âgées.
Keywords: Loneliness; Health and wellbeing; Elderly